2021
DOI: 10.1177/13694332211009320
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of reinforced concrete beams made by innovative post-filling coarse aggregate process

Abstract: Concrete made by post-filling coarse aggregate process could reduce the cement content greatly compared with traditional concrete placement method. Thus, it not only lowers the production cost of concrete through lower usage of cement but also reduces the CO2 emissions to the environment. In this paper, the compressive and tensile strength of post-filling coarse aggregate concrete with different post-filling ratios (PFRs) (0%, 10%, 15%, 20%, 25%, 30%) and concrete strength grades (C30, C40, C50) were first stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It was suggested that the post-filling ratio of coarse aggregate for C30 concrete is 20%. Jia et al 23 studied the flexural performance of the post-filling aggregate concrete research and results shows that the average strain of the normal section of the postfilling aggregate concrete beam conforms to the plane section assumption. The flexural failure phenomenon of post-filling aggregate concrete beam is similar to that of reference concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the post-filling ratio of coarse aggregate for C30 concrete is 20%. Jia et al 23 studied the flexural performance of the post-filling aggregate concrete research and results shows that the average strain of the normal section of the postfilling aggregate concrete beam conforms to the plane section assumption. The flexural failure phenomenon of post-filling aggregate concrete beam is similar to that of reference concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Although the basic properties, flexural and shear properties of beams as well as axial compression and eccentric compression of columns specimens have been investigated, 1,[22][23][24][25][26] the seismic behavior of beam-column joint made of post-filling coarse aggregate concrete has not been reported. It is crucial to study and understand the seismic behavior of post filling coarse aggregate to facilitate its application in engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For the theoretical calculation of the flexural performance of concrete beams in this aspect of research, Du et al (Du et al 2021) carried out a theoretical analysis of the flexural performance of alkali-activated concrete beams. And Jia et al (Jia et al 2021) carried out a theoretical analysis of the flexural performance of concrete beams with the coarse aggregate post-filling process. But at present, there is no relevant theoretical analysis of the flexural performance of steel fiber reinforced gangue concrete beam, which has brought inconvenience to the application of engineering structural designers.…”
Section: Introductionmentioning
confidence: 99%